Upaya Meningkatkan Hasil Belajar Siswa Dalam Pembelajaraan IPS Melalui Model Pembelajaran Aktif Tipe Giving Question And Getting Answer Pada Siswa Kelas V SDN No. 14 Inpres Cikowang - Sulvahrul Amin; Yumrian Yumrian; Aldea Taisa (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The main problem in this research is whether the use of the Giving Question and Getting Answer Learning Model can improve student learning outcomes in Class V Social Sciences learning at SDN No. 14 Cikowang Presidential Instruction. This research aims to improve student learning outcomes by using the Giving Question and Getting Answer Learning Model in Class V Social Sciences learning at SDN No. 14 Cikowang Presidential Instruction. This type of research is Classroom Action Research (PTK) which consists of two cycles. This research procedure includes planning, implementing actions, observing and reflecting. The subjects in this research were fifth grade students at SDN No. 14 Inpres Cikowang as many as 15 people. The results of the research showed that in the first cycle only 6 out of 15 students or 40% completed the KKM and obtained an average score of 55.53. Meanwhile, in cycle II, out of 15 students, 12 students or 80% had fulfilled the KKM, namely the average score obtained was 85.00%. Based on the results of the research above, it can be concluded that student learning outcomes in social studies subjects for class V SDN No. . 14 of Presidential Instruction Cikowang through the application of the Giving Question and Getting Answer learning model has increased.